The role of wild bees and cavity‐nesting wasps as ecological indicators of the last traditionally managed meadows in Eastern Europe - Imre Demeter; Károly Lajos; Adalbert Balog; Miklós Sárospataki (Ecology and Evolution)
Abstract The number of wild bees and cavity‐nesting wasps is abundant in agricultural areas and they contribute significantly to ecosystem services. Due to their specialization in nesting sites and food sources, these groups are sensitive to habitat condition changes and they are therefore important indicators for environmental impact assessments. As semi‐natural habitats are steadily declining and often understudied, their significance for research is increasingly recognized. During this research, the role of wild bee species and cavity‐nesting Hymenopteran taxa as indicators was examined, along the unique combination of high nature value and traditional land use habitats in Eastern Europe, Transylvania. Transects and trap nests were used to test the diversity and abundance of wild bees and cavity‐nesting Hymenopterans to identify possible differences between highly protected and less protected areas. The differences in taxonomic groups between the sites and the potential effects of landscape structure on wild bees and cavity‐nesting Hymenopterans were also assessed. We detected a high diversity of wild bee species and a significant species replacement from one study year to another. Among the nest‐building Hymenopteran taxa, the majority of nests was built by Trypoxylon sp. during both study years, with a stronger dominance in the second year. The different taxonomic groups of wild bees and cavity‐nesting Hymenopterans showed differences in their habitat affinities. The majority of the sampled bumblebee species as well as Trypoxylon sp. had an affinity towards the study sites located within the highly protected study area. Altogether, we found different habitat preferences for different Hymenopteran groups (both wild bees and wasps) and conclude that these groups definitely have the potential to serve as indicators for differences in the intensity of land use.